SISTEM INFORMASI PENILAIAN KINERJA PEGAWAI MENGGUNAKAN MS VISUAL STUDIO DAN MS ACCESS DI BTC FASHION MALL - Ardi Taryanto Ardi; Rony Riadi (INFOKOM (Informatika & Komputer), 2022)
This study aimed to analyze, design and implement an information system for evaluating employee performance at BTC Fashion Mall. From the research that has been done, there are factors that hinder the employee performance appraisal system because they still use Microsoft Office Excel which is felt to be less effective and efficient. The research method uses qualitative methods with data collection techniques used are direct observation, interviews and literature review.. In designing this employee performance appraisal information system, the author uses an object-oriented approach with UML (Unified Modeling Language) modeling, and is implemented with Microsoft Visual Studio 2010 and Microsoft Access programming languages, and uses the Prototype software development method. With this application as a means of processing employee performance appraisals, it is hoped that the processing of employee performance appraisal data can run quickly and optimally.